2014
DOI: 10.17795/ajdr-21195
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chlorhexidine on Push-out Bond Strength of Mineral Trioxide Aggregate

Abstract: Background: Trioxide Aggregate (MTA) has been widely used in root canal therapy. MTA has been mixed with chlorhexidine to increase its antimicrobial effect. Objectives: The aim of this study was to evaluate the effect of chlorhexidine (2%) on push-out bond strength of Mineral Trioxide Aggregate (MTA). Materials and Methods:Sixty dentin disks with a thickness of 1.5 ± 0.2 mm and lumen size of 1.3 mm were prepared. Dentin disks were randomly divided into four groups (n = 15), and their lumens were filled with MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…It should be easy to manipulate and should be radiopaque, among other requirements, addition to these properties, it must be dimensionally stable, non-resorbable, and impervious to moisture. 4 Bioceramic root end filling material has shown to have success rate 86.4-95.6 in the last years and its showed high success rate in comparison to amalgam [2]. MTA was tested extensively in many vivo and vitro studies over the last years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be easy to manipulate and should be radiopaque, among other requirements, addition to these properties, it must be dimensionally stable, non-resorbable, and impervious to moisture. 4 Bioceramic root end filling material has shown to have success rate 86.4-95.6 in the last years and its showed high success rate in comparison to amalgam [2]. MTA was tested extensively in many vivo and vitro studies over the last years.…”
Section: Discussionmentioning
confidence: 99%
“…3 Root end filling material should be antimicrobial, nontoxic, and biocompatible, radiopaque, non-resorbable, dimensionally stable, resist dislocating forces, withstand breakdown or dissolution by tissue fluids, be easily handled, and be able to adapt to the dentinal walls of root canal system . 4 Numerous materials had been used as root end filling material, Amalgam is one of the most used root-end filling materials its remain the standard to which other materials are evaluated .It is durable, less technically sensitive, easy to handle, has minimal technical time compared to other materials and its corrosion products seal the apex surface and prevent leakage of bacteria. Some of the disadvantages are local allergic reactions, mercury toxicity and lack of chemical bonding with dentin.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that CHX has no adverse effect on setting process of MTA and the push out bond strength of MTA/H 2 O was not significantly different from MTA/CHX. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…However, it cannot simulate the thermal cycles of the mouth, dietary regimen, or the salivary flow. [ 18 20 22 ]…”
Section: Discussionmentioning
confidence: 99%